An improved hybrid model for shoreline change - Lakku, Naresh Kumar Goud; Chowdhury, Piyali; Behera, Manasa Ranjan (Frontiers in Marine Science, 2024)
Predicting the nearshore sediment transport and shifts in coastlines in view of climate change is important for planning and management of coastal infrastructure and requires an accurate prediction of the regional wave climate as well as an in-depth understanding of the complex morphology surrounding the area of interest. Recently, hybrid shoreline evolution models are being used to inform coastal management. These models typically apply the one-line theory to estimate changes in shoreline morphology based on littoral drift gradients calculated from a 2DH coupled wave, flow, and sediment transport model. As per the one-line theory, the calculated littoral drift is uniformly distributed over the active coastal profile. A key challenge facing the application of hybrid models is that they fail to consider complex morphologies when updating the shorelines for several scenarios. This is mainly due to the scarcity of field datasets on beach behavior and nearshore morphological change that extends up to the local depth of closure, leading to assumptions in this value in overall shoreline shift predictions. In this study, we propose an improved hybrid model for shoreline shift predictions in an open sandy beach system impacted by human interventions and changes in wave climate. Three main conclusions are derived from this study. First, the optimal boundary conditions for modeling shoreline evolution need to vary according to local coastal geomorphology and processes. Second, specifying boundary conditions within physically realistic ranges does not guarantee reliable shoreline evolution predictions. Third, hybrid 2D/one-line models have limited applicability in simple planform morphologies where the active beach profile is subject to direct impacts due to wave action and/or human interventions, plausibly due to the one-line theory assumption of a constant time-averaged coastal profile. These findings provide insightful information into the drivers of shoreline evolution around sandy beaches, which have practical implications for advancing the shoreline evolution models.